Community-based HIV prevention services for transgender people in Ukraine: current situation and potential for improvement - Oleksandr Neduzhko; Tetiana Saliuk; Oksana Kovtun; Nadiia Semchuk; Olga Varetska (BMC Health Services Research, 2023)
Abstract Background Community-based HIV-prevention services are a key approach to prevent HIV transmission among key population representatives. Transgender people have multiple specific needs and it is crucial to use prevention approaches that effectively respond to those needs and facilitate barriers on the way to use HIV prevention and related services. This study is aimed to explore the current state of community-based HIV prevention services among transgender people in Ukraine, its limitations and potential for improvement based on the experience and perceptions of transgender people, physicians, and community social workers providing services to transgender people. Methods Semi-structured in-depth interviews were conducted among physicians providing services to transgender people (N = 10), community social workers (N = 6), and transgender people (N = 30). The objectives of the interviews were to explore: the relevance of the community-based HIV prevention services to the needs of transgender people; the key components of the most preferred (“ideal”) HIV-prevention package for transgender people; ways to optimize the existing HIV prevention package for transgender people including enrollment and retention. Systematically collected data were analyzed and coded into the main domains, thematic categories and subcategories using thematic analysis. Results The current HIV prevention programs were well-evaluated by the majority of respondents. Gender-affirming care was found to be the key need of transgender people. Integration of HIV prevention services and gender-affirming care was perceived as the main way to address the needs of transgender people. Internet-based and peer word-of-mouth recruitment may improve enrollment in services. Optimization of existing HIV prevention package may include: psychological counseling, referral and navigation to medical services, legal services, pre- and post-exposure prevention, dissemination of tube lubricants, femidoms and latex wipes, use of oral fluid test systems for HIV self-testing. Conclusions The findings of this study suggest potential solutions to improve community-based HIV prevention services for transgender people by introducing a transgender people -oriented package, which integrates gender transition, HIV prevention and other services. Provision of prevention services based on assessed risk and referral/navigation to related services are the key options for optimization of the existing HIV prevention package. Trial registration Not applicable.